Decision-makers impact on the internationalization of high-technology firms in emerging markets - Michael Neubert; Augustinus Stijn Van Der Krogt (Journal of Global Entrepreneurship Research, 2019)
This study examines the impact of decision-makers from Paraguayan software firms on internationalization. It aims to have a better understanding about the (non-) rational decision logic of the CEOs and founders shaping the internationalization processes of 45 Paraguayan software firms. This study uses an observational, comparative descriptive, and a descriptive, correlational-research design based on a survey with the CEOs and founders of 45 Paraguayan software firms. The results suggest a significant correlational impact of decision-makers' characteristics on the software firm's internationalization and calls for further collaboration with high-tech firms from different industries in emerging as well as developed markets.
Keywords: 650; International entrepreneurship; High-tech firms; Uppsala model; Paraguay; Decision-making; Internationalization; Emerging markets